Building energy flexibility: a sensitivity analysis and key performance indicator comparison. (November 2019) - Johra, Hicham; Marszal-Pomianowska, Anna; Ellingsgaard, John Ray; Liu, Mingzhe
Abstract: Buildings are a key active element of the future Smart Grids with large shares of renewable energy, as they can provide flexible energy usage to help balancing power production intermittence. There is currently no consensus yet on how to quantify building energy flexibility. The various KPIs found in literature can be classified into 4 main categories: load shifting ability, power adjustment, energy efficiency and cost efficiency. Most of them use a reference scenario. Moreover, the envelope performance appears to be the most important parameter with regards to all aspects of building energy flexibility when using indoor temperature set point modulation.